Arsenic leached by step-wise ions addition under aerobic and anaerobic: Speciation by Sequential Hydride Generation Flow Injection Analyzer (SHGFIA) - Hashem, MA; Toda, K (Bangladesh Journal of Scientific and Industrial Research, 2015)
Leaching behavior of arsenic has been investigated by step-wise ions addition of river sediment near arsenic mine; arsenic was contained in sediment 450 mg kg-1. Leachates were characterized by discriminating arsenite and arsenate under both aerobic and anaerobic. Results indicate that arsenite As(III) and arsenate As (V) were leached from the sediments by step-wise ions addition especially phosphate ion enhanced more leaching of arsenic from sediment under anaerobic mostly was As (V). DOI: http://dx.doi.org/10.3329/bjsir.v49i3.22135 Bangladesh J. Sci. Ind. Res. 49(3), 195-198, 2014